Correlation between bursting pressure and breaking strength in colonic anastomosis - Durães, Leonardo de Castro (2013)
PURPOSE: To investigate the correlation between bursting pressure and breaking strength on the 7th postoperative day following left colonic anastomosis in rats. METHODS: Seventy rats were randomly divided into seven groups of ten animals each. All of the animals underwent segmental resection of the left colon and end-to-end anastomosis. The animals in groups I to VI underwent surgical laparoscopies with pneumoperitoneums using carbon dioxide or helium at pressures of 5, 12 or 20 mmHg. In Group VII, open laparotomy was performed. The animals were reoperated on postoperative day 7 to measure the bursting pressure and the breaking strength of the anastomosis. RESULTS: The anastomosis bursting pressure in 70 animals was 193.10±55.56 mmHg. There was no significant difference between the groups (p=0.786). The breaking strength of the anastomosis was 0.26±0.12 N. There was no significant difference between the groups (p=0.356). Pearson's correlation test showed a low correlation (r=0.231) lacking statistical significance (p=0.054). CONCLUSION: There was no correlation between the bursting pressure and breaking strength of left colonic anastomoses in rats on the 7th postoperative day.